2021
DOI: 10.1136/bmj.n1135
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admission and mortality rates for non-covid diseases in Denmark during covid-19 pandemic: nationwide population based cohort study

Abstract: Objective To determine the incidence of hospital admissions and associated mortality rates for non-covid medical conditions during the covid-19 pandemic. Design Nationwide, population based cohort study. Setting Denmark from 13 March 2019 to 27 January 2021. Participants All Danish residents >1 year of age. Main outcomes measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
143
3
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 28 publications
18
143
3
8
Order By: Relevance
“…15 Recently, Bodilsen et al in a Danish nationwide cohort study involving more than 1 million of hospital admissions, found that compared with the pre-COVID baseline period (mean hospital admission rate 204.1 per 100,000/week), the overall hospital admission rate for non COVID-19 conditions was reduced to 142.8 per 100,000/week after the first national lockdown, followed by a gradual return to baseline state until the second lockdown when it decreased to 158.3 per 100,000/week. 16 The second most interesting findings of our study is that the decrease of admissions (non-COVID) was statistically significant during the peak-COVID and late-COVID periods but not the early-COVID period during the two waves compare to pre-COVID period. The decrease was in most of the type of admissions but some were significantly affected by the crisis depending on restrictive measures undertaken at the country and hospital levels.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…15 Recently, Bodilsen et al in a Danish nationwide cohort study involving more than 1 million of hospital admissions, found that compared with the pre-COVID baseline period (mean hospital admission rate 204.1 per 100,000/week), the overall hospital admission rate for non COVID-19 conditions was reduced to 142.8 per 100,000/week after the first national lockdown, followed by a gradual return to baseline state until the second lockdown when it decreased to 158.3 per 100,000/week. 16 The second most interesting findings of our study is that the decrease of admissions (non-COVID) was statistically significant during the peak-COVID and late-COVID periods but not the early-COVID period during the two waves compare to pre-COVID period. The decrease was in most of the type of admissions but some were significantly affected by the crisis depending on restrictive measures undertaken at the country and hospital levels.…”
Section: Discussionsupporting
confidence: 46%
“…Our results on non-COVID in-hospital admissions are in line with those published in the literature. [9][10][11][12][13][14][15][16] Birkmeyer et al found in a large study of approximately one million medical admissions in the US that declines in non-COVID admissions from the first two months of COVID crisis exceeded 20% for all primary admission diagnoses. 9 Kapsner et al found that overall in-patient hospital admissions in Germany decreased by 35% in the first month and by 30.3% in the second month after the lockdown announcement during the first wave compared to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many studies assessing the effect of COVID-19 on the presentation of other conditions [23][24][25], there are few reports on the effect of COVID-19 on the outcomes of non-COVID critically ill patients or assessing the impact on ICU performance. A recent nationwide study in Denmark reported that outcomes of several acute conditions on hospitalized patients, including those with sepsis and cancer, were worst during COVID-19 pandemic [26]. Although not focused specifically on critically ill patients, conditions whose outcomes were more impaired during COVID-19 were unsurprisingly those requiring more urgent care.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly people and individuals with pre-existing chronic medical conditions are at increased risk of morbidity and mortality due to COVID-19 [23,24]. However, excess deaths, including out-of-hospital deaths, from non-COVID conditions such as cancer, diabetes, dementia, hypertension and heart disease have occurred during the pandemic [25][26][27][28]. Thus, COVID-19 has particular implications for the ability of vulnerable populations to access healthcare, as they will need to balance specific care needs against a heightened risk of contracting the disease.…”
Section: Introductionmentioning
confidence: 99%